KORELASI CRP DENGAN HEMOKONSENTRASI DAN NILAI TROMBOSIT PADA ANAK DENGAN DBD DAN DD - Maduwu, El Yoenay Ivanema; Silaen, Johan Christian; Simaremare, Ade Pryta (Jurnal Visi Eksakta, 2023)
Dengue is a disease commonly found in tropical and subtropical regions, with its main vector of transmission being the Aedes aegypti mosquito. Common symptoms experienced by dengue patients include fever followed by severe headache, retro-orbital pain, nausea, vomiting, fatigue, and typically a rash due to minor bleeding. In acute infections, CRP is often used to assess disease activity causing inflammation and can be one of the inflammatory biomarkers in dengue patients. To examine the correlation between CRP levels, hemoconcentration, and platelet count in children diagnosed with Dengue. This study is an observational analytical study using a cross-sectional approach and data collection through consecutive sampling with a total sample size of 60 individuals. In this study, there were 60 pediatric patients diagnosed with Dengue Hemorrhagic Fever (DHF) and Dengue Fever. Most of 34 patients (56.7%) were male, while 26 patients (43.3%) were female. The majority of DHF and Dengue Fever patients were aged between 5 and 11 years (63.3%). The Chi-Square test analysis between CRP and hematocrit showed p=0.486. The Chi-Square test analysis between CRP and platelet count showed p=0.042 (p<0.005). CRP has no correlation with hemoconcentration, but correlate with trombositopenia level in pediatric patients with Dengue Hemorrhagic Fever and Dengue Fever.